TWO PHASE CFD FLOW ANALYSIS OF R134a AND R1234yf REFRIGERANTS AND ITS EFFECT ON COOLING PERFORMANCE IN AN AUTOMOBILE HVAC EVAPORATOR CORE - P, Tamilselvan; Samuel, Anand A; Rajamanickam, C S (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The purpose of this research is to conduct a two-phase fluid analysis and simulation for examining the influence of refrigerant (R134a/R1234yf) properties on cooling performance of an automobile HVAC (Heating, Ventilation and Air Conditioning) evaporator core and compare their performances. In this research, streamline deviation, static pressure, velocity magnitude, pressure co-efficiency, Reynolds number and turbulent kinetic energy play a key role in the comparison of the refrigerants R1234yf and R134a two-phase fluids. Subsequently, it was found that R134a properties were better towards the cooling performance of an automobile HVAC evaporator core.